2002
DOI: 10.1029/2001jb000355
|View full text |Cite
|
Sign up to set email alerts
|

Control of folding by gravity and matrix thickness: Implications for large‐scale folding

Abstract: [1] We show that folding of a non-Newtonian layer resting on a homogeneous Newtonian matrix with finite thickness under influence of gravity can occur by three modes: (1) matrix-controlled folding, dependent on the effective viscosity contrast between layer and matrix, (2) gravitycontrolled folding, dependent on the Argand number (the ratio of the stress caused by gravity to the stress caused by shortening), and (3) detachment folding, dependent on the ratio of matrix thickness to layer thickness. We construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 52 publications
3
89
0
Order By: Relevance
“…The Argand number Ar N is similar to the one that has been introduced by England and McKenzie (1982) to scale the gravitational stress to the horizontal stress during lithospheric thickening and is similar to the Argand number applicable to lithospheric folding (Schmalholz et al, 2002). Fletcher and Hallet (1983) showed that for a wide range of creep flow laws and an extension rate of the order of 10 −15 s −1 , the necking instability is strong (α d 40) and that the dominant wavelength L d = 30-90 km.…”
Section: Lithospheric Neckingmentioning
confidence: 80%
See 3 more Smart Citations
“…The Argand number Ar N is similar to the one that has been introduced by England and McKenzie (1982) to scale the gravitational stress to the horizontal stress during lithospheric thickening and is similar to the Argand number applicable to lithospheric folding (Schmalholz et al, 2002). Fletcher and Hallet (1983) showed that for a wide range of creep flow laws and an extension rate of the order of 10 −15 s −1 , the necking instability is strong (α d 40) and that the dominant wavelength L d = 30-90 km.…”
Section: Lithospheric Neckingmentioning
confidence: 80%
“…The dominant wavelength for viscous and power-law viscous layers resting on an inviscid medium under gravity is the same (Schmalholz et al, 2002). Values of n for dislocation creep are usually in the range 3-5.…”
Section: Lithospheric Foldingmentioning
confidence: 99%
See 2 more Smart Citations
“…In some areas, the subsidence events are related to lithosphere extension, thermal subsidence and crustal buckling/folding (e.g. Lambeck 1983;Burg & Podladchikov 1999;Cloetingh et al 2002;Schmalholz et al 2002). In other basins, the subsidence mechanism is less clear, and some intracratonic basins have been linked to processes that originate in the mantle (e.g.…”
Section: Examples Of Intraplate Deformation Induced By Lithosphere Rementioning
confidence: 99%